Tao bilang Tagpuan: Roque Ferriols, San Agustin, at ang Puntong Omega - Calano, Mark Joseph T (Archīum Ateneo, 2018)
In his book Pilosopiya ng Relihiyon, Roque Ferriols argued that the encounter between God and the human person can be concretely experienced in the attempt of being human. What does he mean by this statement? This paper tries to understand this statement in three parts. The first part analyzes Ferriols’s assertion of the role of damdamin, the personal nature of God, and our encounter with others and God. In trying to understand this relational (rather than conceptual) encounter with God, we move to Augustine of Hippo’s discussion of remembering, knowing, and willing (or loving) as the mental faculties that are reflective and analogical of the Trinity in the human person; the second part situates the discourse within a Christian narrative that argues for Christ as the exemplar and fullness of humanity. The third part discusses Ferriols’s treatment of Teilhard de Chardin’s Omega Point, where evolution leads us to further creation instead of destruction; this part connects with the second part in that Ferriols (drawing from de Chardin) speaks of the Omega Point as ‘possibly’ referring to Christ. It further discusses how we are invited into this personal love that unites and creates us in the process of being more human.